EFFECT OF NUTRIENT SOLUTION CONCENTRATION ON THE GROWTH PERFORMANCE OF PAKCOY MUSTARD (Brassica rapa L.) UNDER A SENSOR-BASED NUTRIENT FILM TECHNIQUE HYDROPONIC SYSTEM - Hardjo, Popy Hartatie; dos Santos, Zelia Camoes; Sugiarno, Stefan Saputra; Plessers, Timothy Amadeus Filhend (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
The growth of pakcoy mustard (Brassica rapa L.) is strongly influenced by the concentration and composition of hydroponic nutrient solutions. This study aims to determine the optimal nutrient solution concentration for maximized pakcoy mustard growth at harvest. The experimental setup adopted was a randomized block design featuring 5 different levels of electrical conductivity (EC), specifically 0.8 mS.cm-1, 1.2 mS.cm-1, 1.6 mS.cm-1, 2.0 mS.cm-1, and 2.4 mS.cm-1, with replicated ten times. The parameters evaluated to assess the efficacy of each treatment include plant height, number of leaves, leaf area, overall fresh weight of the plant, and chlorophyll levels. Data were analyzed using Duncan Multiple Range Test (DMRT) at a 5% significance level(p < 0.05). The results indicated that an EC of 2.0 mS.cm-1 led to the greatest growth of pakcoy mustard, achieving a plant height of 9.6±2.38 cm, a leaf count of 23.9±2.13, a leaf area of 32.81±8.95 cm2, and a chlorophyll concentration of 5.9±0.52 mg.l-1with a harvest period of four weeks.